2023
DOI: 10.1186/s41073-023-00133-5
|View full text |Cite|
|
Sign up to set email alerts
|

Fighting reviewer fatigue or amplifying bias? Considerations and recommendations for use of ChatGPT and other large language models in scholarly peer review

Abstract: Background The emergence of systems based on large language models (LLMs) such as OpenAI’s ChatGPT has created a range of discussions in scholarly circles. Since LLMs generate grammatically correct and mostly relevant (yet sometimes outright wrong, irrelevant or biased) outputs in response to provided prompts, using them in various writing tasks including writing peer review reports could result in improved productivity. Given the significance of peer reviews in the existing scholarly publicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The conversational prowess of AI authoring tools could facilitate the editorial and peer reviewer process by helping to craft summaries and even decisions more quickly 23 . Some have even suggested that these tools could help address a shortage of peer reviewers 24 . However, Hosseini and Horbach 24 expressed concerns about the opacity of proprietary models and their training data, inner workings, and the potential for exacerbating existing biases.…”
Section: Can Ai Tools Be a Peer Reviewer?mentioning
confidence: 99%
See 1 more Smart Citation
“…The conversational prowess of AI authoring tools could facilitate the editorial and peer reviewer process by helping to craft summaries and even decisions more quickly 23 . Some have even suggested that these tools could help address a shortage of peer reviewers 24 . However, Hosseini and Horbach 24 expressed concerns about the opacity of proprietary models and their training data, inner workings, and the potential for exacerbating existing biases.…”
Section: Can Ai Tools Be a Peer Reviewer?mentioning
confidence: 99%
“…Some have even suggested that these tools could help address a shortage of peer reviewers 24 . However, Hosseini and Horbach 24 expressed concerns about the opacity of proprietary models and their training data, inner workings, and the potential for exacerbating existing biases. Thus, they argue that like authors, reviewers, and editors should also disclose their use.…”
Section: Can Ai Tools Be a Peer Reviewer?mentioning
confidence: 99%
“…However, they concluded that "the fundamental opacity of LLMs' training data, inner workings, data handling, and development processes raise concerns about potential biases, confidentiality and the reproducibility of review reports." 4 JAMA and the JAMA Network journals have extended the policy on use of AI tools to peer reviewers with recommendations for responsible and accountable use and reminders of the confidential nature of submitted manuscripts and the peer review process. These journals use a single-anonymized review process, in which peer reviewer identities are kept confidential (unless reviewers choose to reveal their names in their formal reviews), author identities are made known to reviewers, and submitted manuscripts and other content are kept confidential if and until publication.…”
mentioning
confidence: 99%
“…Hosseini and Horbach recently reviewed the potential use of LLMs in the peer review process following Tennant and Ross-Hellauer’s 5 core themes about peer review: the reviewers’ role, the editors’ role, functions and quality of peer reviews, reproducibility, and the social and epistemic functions of peer reviews. They identified potential benefits of these tools to improve efficiency and productivity in the editorial process and peer review and help with reviewer fatigue.…”
mentioning
confidence: 99%
See 1 more Smart Citation